Conformational dynamics of cathepsin D and binding to a small‐molecule BACE1 inhibitor. Issue 15 (2nd April 2017) - Ellis, Christopher R.; Tsai, Cheng‐Chieh; Lin, Fang‐Yu; Shen, Jana
Abstract : BACE1 is a major therapeutic target for prevention and treatment of Alzheimer's disease. Developing inhibitors that can selectively target BACE1 in favor of other proteases, especially cathepsin D (CatD), has presented significant challenges. Here, we investigate the conformational dynamics and protonation states of BACE1 and CatD using continuous constant pH molecular dynamics with pH replica‐exchange sampling protocol. Despite similar structure, BACE1 and CatD exhibit markedly different active site dynamics. BACE1 displays pH‐dependent flap dynamics that controls substrate accessibility, while the CatD flap is relatively rigid and remains open in the pH range 2.5–6. Interestingly, although each protease hydrolyzes peptide bonds, the protonation states of the catalytic dyads are different within the active pH range. The acidic and basic components of the BACE1 catalytic dyad are clear, while either aspartic acid of the CatD catalytic dyad could play the role of acid or base. Finally, we investigate binding of the inhibitor LY2811376 developed by Eli Lilly to BACE1 and CatD. Surprisingly, in the enzyme active pH range, LY2811376 forms a stronger salt bridge with the catalytic dyad in CatD than in BACE1, which might explain the retinal toxicity of the inhibitor related to off‐target inhibition of CatD. This work highlights the complexity and challenge in structure‐based drug design where receptor‐ligand binding induces protonation state change in both the protein and the inhibitor. © 2017 Wiley Periodicals, Inc. Abstract : BACE1 is a major therapeutic target for Alzheimer's disease. Developing selective inhibitors has presented significant challenges. Here, we use continuous constant pH molecular dynamics simulations to investigate the conformational dynamics of cathepsin D (CatD) and its binding to a BACE1 inhibitor as a function of pH. Surprisingly, in the enzyme active pH range, the inhibitor forms a stronger salt bridge with the catalytic dyad in CatD than in BACE1, which might explain the off‐target inhibition of CatD. Our work highlights the importance of incorporating pH effects in structure‐based drug design.